GC-MS Identification and Quantification of the Synthetic Cannabinoid MDMB-4en- PINACA in Cannabis-derived Material Seized in the Turin Metropolitan Area (Italy) - Gerace, Enrico; Seganti, Fabrizio; Di Corcia, Daniele; Vincenti, Marco; Salomone, Alberto (Current Pharmaceutical Design, 2022)
Background: The presence of the synthetic cannabinoid receptor agonist MDMB-4en-PINACA in adulterated low-THC cannabis products was recently highlighted in several reports. Moreover, numerous intoxication cases involving MDMB-4en-PINACA have been described. Objective: In order to monitor the diffusion of cannabis products containing MDMB-4en-PINACA in our territory, a total of 358 cannabis-derived samples (213 vegetal material and 145 resins) seized in the period November 2020 - February 2021 in the western Piedmont Area (Italy) was analyzed. Methods: General screening analyses for traditional and synthetic cannabinoids were performed by a GC-MS device operating in full scan mode (40-600 amu). The MDMB-4en-PINACA was quantified by means of a specific GC-SIM-MS protocol purposely developed and validated, while the quantification of THC, CBD, and CBN was carried out by a GC-SIM-MS method routinely employed in our laboratory. Results: MDMB-4en-PINACA was detected in 12 out of 358 samples (3.4% of the total). Among these, the molecule was found in 11 vegetal materials and in one resin sample. Considering solely the analysis of the 213 herb products, a positive rate of 5.2% was found for the presence of MDMB-4en-PINACA in these samples. MDMB-4en-PINACA was found in the seized materials at concentration levels ranging from 0.4 up to 6.3 mg/g (mean 2.5 mg/g; median 1.7 mg/g). Concerning the traditional cannabinoids, the THC concentration was in the interval 3-43 mg/g (mean 12 mg/g; median 7 mg/g), while CBD was found at higher concentrations in all specimens, specifically in the range 47-140 mg/g (mean 87 mg/g; median 80 mg/g). Conclusion: The adulteration of low-THC cannabis products with synthetic cannabinoid receptor agonists is widespread today. Since these substances are potentially more toxic than THC, their consumption poses a high risk of overdose for unaware users and a health-threatening situation. This study confirmed the sporadic presence on the market of CBD-prevalent cannabis products adulterated with MDMB-4en-PINACA.
Keywords: MDMB-4en-PINACA